OEFFICIENT ESTIMATES OF NEW SPECIAL SUBCATEGORY OF BI-UNIVALENT FUNCTIONS - Mohammed, Kosrat O.; Abdullah, Khalid I.; Mohammed, Nafya H.; Adarbar, Abubakr M.; Sharifi, Hedayat M. (Science Journal of University of Zakho, 2024)
In the present paper, we introduce and investigate a new subcategory H_Σ (q,β;ς) of analytic and bi-univalent functions in the open unit disk  D based on the ideas of q-derivative operator and subordination. For the functions belong to the subcategory H_Σ (q,β;ς) , upper bounds for the second and third coefficients are found and some special outcomes of the main result are also presented.
Keywords: Analytic Function; Bi-univalent Function; q-derivative; Subordination